Assessment of Reinforced Recycling Aggregate Concrete Beams Under Torsional Moment - F. Sarsam, Kaiss; Salih, Nisreen; Hussein, Mazin (International Journal of Engineering and Technology, 2018)
The recycling of aggregate concrete (RAC) is the ideal solution for reducing the natural resources. The experimental works have been carried out to investigate the torsional moment behavior and the strength of RAC beams in comparison with those  beams consisting of natural aggregate concrete (NAC). Nine beams were casted with different compression strengths of concrete (25, 45, and 70 MPa), and coarse RAC of three different percentages within the full bloc of coarse aggregate in concrete mixes (0, 50, and 100%), with the same reinforcement ratio. The properties of the concrete comprised of recycled and natural aggregates were investigated. The results showed, that the difference in the torque of first crack is less than 12.5% for RAC and NAC beams, while the difference in ultimate torque is less than 7.7% for RAC and NAC. Also, it can be conclude that, the torsional moment performance of RAC beams is acceptable as compared to the conduct of NAC beams and the use of RAC is practically possible
Keywords: Reinforced concrete beam; Recycled aggregates; Torsional moment behavior